O protagonismo negro em personagens de contos de Conceição Evaristo: uma proposta didático-pedagógica em consonância às leis 10.639/03 e 11.645/08 - Santos, Edilma dos (2021)
This monograph, “Protagonismo Negro em Personagens de Contos de Conceição Evaristo: Uma Proposta Didático-Pedagógica em Consonância às Leis 10.639/03 e 11.645/08”, anchored in the referred legal provisions that made the teaching of African, Afro-Brazilian history and culture and indigenous at school, proposes reading strategies so that 9th grade students of elementary school recognize the black protagonism and its social stigmas in the perspective of Black Brazilian Literature by Luis Silva Cuti. Likewise, it promotes the freedom of expression of the student subject reader. Therefore, as a corpus of the research, it is proposed to read three short stories by Conceição Evaristo, namely: “Zaíta, você esqueceu de guardar os brinquedos”, “Lumbiá”, and “Ayoluwa, alegria do nosso povo”, all from the work Olhos D'Água (2018). In this sense, a didactic sequence was prepared in pedagogical notes, a priori, to be developed at the public school Professora Glorita Portugal in São Cristóvão’s city, state of Sergipe, however, with the advent of the COVID-19 pandemic, it was not possible to apply it. It wasn’t choosing this action, in view of the difficulties faced by students in adhering to remote education, however, not retiring to this pedagogical action for teaching literary reading at school. Methodologically supported in a qualitative and interventional way in which theory and practice complement each other, the study had as theoretical support ALMEIDA (2019), the conception of Black-Brazilian Literature of CUTI (2010), COSSON (2009), DALCASTAGNÈ (2005), EVARISTO (2009), FREIRE (1992), KOCH (2008), MACHADO (2005), RIBEIRO (2017), ROUXEL (2014), SOLÉ (2014), among others. In addition, to the aim of developing students' literary reading competence from the perspective of a reading subject, at the same time that issues of an ethnic-racial order were discussed, which is often ignored in school life and in our current society. This work seeks to promote the formation of citizens aware of their role as a reader and as a builder of a democratic, anti-racist and more humane society.